KEADILAN EKONOMI ISLAM DI TENGAH DISRUPSI DIGITAL: REFLEKSI PEMIKIRAN IBNU TAIMIYAH - Nurhidayani Pulungan; Sarmiana Batubara (Program Studi Ekonomi Syariah Sekolah Tinggi Agama Islam Negeri Mandailing Natal, 2025)
Abstract This study aims to analyze Ibn Taymiyyah's thoughts on Islamic economic justice and examine their relevance in the context of today's digital disruption. Furthermore, this study aims to provide recommendations for economic policies based on the principles of Islamic justice that can be applied to address the challenges of the digital economy. The approach used in this study is qualitative with literature analysis. Data were collected through a review of Ibn Taymiyyah's works, particularly those related to the concept of economic justice, as well as literature related to digital disruption and Islamic economics. The analytical method used is hermeneutic to interpret the messages in Ibn Taymiyyah's thoughts and compare them with developments in the digital economy. The results show that the principles of economic justice promoted by Ibn Taymiyyah are highly relevant for application in addressing the inequalities arising from digital disruption. The concepts of equitable wealth distribution, protection of individual rights, and transparency in economic transactions can serve as guidelines in designing more inclusive economic policies. Although Ibn Taymiyyah does not directly address digital disruption, the concepts proposed can be adapted to create balanced and equitable policies.